2007
DOI: 10.1002/mop.22696
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically coupled microstrip square/circular ring resonators: Inset/offset feed variation effects on resonance frequency

Abstract: Inset/offset feed‐dependent variation of electromagnetically coupled microstrip square and circular ring resonators (MSRR/MCRR) over a wide range indicate overall increase and decrease in resonant frequency (fr) respectively. On the basis of the experimental results, equations are suggested to determine fr as a function of the normalized inset and offset feed positions. Equations are validated for a limited range. High values of quality factor Q = 618 are obtained with MSRR as compared with MCRR (Q = 375) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ghanbari et al [7,8] have reported somewhat similar experimental work (on CRR with EM coupled feed line variation), but only by reflection measurements and their EM coupled feed line terminating inside the ring only. They could not get any splitting (which we have confirmed by simulation for their geometry).…”
Section: Comparison Of Frequenciesmentioning
confidence: 65%
See 2 more Smart Citations
“…Ghanbari et al [7,8] have reported somewhat similar experimental work (on CRR with EM coupled feed line variation), but only by reflection measurements and their EM coupled feed line terminating inside the ring only. They could not get any splitting (which we have confirmed by simulation for their geometry).…”
Section: Comparison Of Frequenciesmentioning
confidence: 65%
“…All the rings were designed for nominally the same frequency of 2.4 GHz for only the ring on a substrate, without considering actual situation of EM coupling geometry, for comparison with the previous reports [7][8][9][10]. This is, however, not very critical in present work, as our main interest is the relative changes, using this as reference, for triangular and square rings chamfering is used at all the corners.…”
Section: Designmentioning
confidence: 96%
See 1 more Smart Citation